2006
DOI: 10.1158/0008-5472.can-05-1636
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Fingerprinting and Autocrine Growth Regulation of Endothelial Cells in a Murine Model of Hepatocellular Carcinoma

Abstract: In a mouse model of hepatocellular carcinogenesis, highly vascularized tumors develop through two distinct morphologic phases of neovascularization. We show that increased vascular caliber occurs first, followed by extensive vessel sprouting in late-stage carcinomas. To define molecular pathways in tumor neovascularization, endothelial cells were directly purified from normal liver and advanced tumors. Gene expression profiling experiments were then designed to identify genes enriched in the vascular compartme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 71 publications
9
62
0
Order By: Relevance
“…The highest levels of Cat S activity were also found in grade IV tumors among 59 astrocytoma biopsies 10 . In murine model of hepatocellular carcinoma, Cat S was the major overexpressed protease during vessel spouting 11 . On the one hand, cysteine cathepsin activity has been functionally implicated in pancreatic islet cells from a mouse model of carcinogenesis 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The highest levels of Cat S activity were also found in grade IV tumors among 59 astrocytoma biopsies 10 . In murine model of hepatocellular carcinoma, Cat S was the major overexpressed protease during vessel spouting 11 . On the one hand, cysteine cathepsin activity has been functionally implicated in pancreatic islet cells from a mouse model of carcinogenesis 12 .…”
Section: Introductionmentioning
confidence: 99%
“…During tumour-induced angiogenesis, the two important vascular cell types, endothelial cells and surrounding pericytes, develop multiple morphological and architectural abnormalities 7,8 as well as altered expression of marker proteins [9][10][11][12] . Using the RIP-Tag mouse model of pancreatic islet carcinogenesis (SV40 large T antigen expressed under the control of the rat insulin gene (Ins2) promoter), we have recently observed that Rgs5 is overexpressed in the aberrant tumour vasculature 10 .…”
mentioning
confidence: 99%
“…Many tumours produce inhibitory cytokines (Mantovani et al, 2004), which could alter the function of endothelium-adhered leucocytes including their ability to extravasate. Studies performed on murine hepatocellular carcinoma showed that impaired migration of lymphocytes to neoplastic liver tissue coincided with elevated production of IL-10 by endothelial cells of tumour neovessels (Ryschich et al, 2006). In this study, we have analysed the expression of IL-10 in 25 of 28 carcinoma specimens and in 29 of 30 NHPG specimens.…”
Section: Resultsmentioning
confidence: 99%
“…In our present study, we were able to detect only CD54 (but not CD106 and CD62E) on prostate blood vessels (Figure 1), whereas percentages of CD54-expressing vessels were significantly higher in carcinoma specimens (in both adenocarcinoma foci and perimalignant benign areas) than in NHPG specimens (Figure 1). Intriguingly, a positive correlation between vascular CD54 and percentage of tissue occupied by leucocyte infiltrate was demonstrated only in benign prostate tissue but not in foci of carcinoma (Table 1) increased vascular expression of CD54 and CD106 was also observed despite the fact that these neovessels were found to inhibit extravasation of lymphocytes (Ryschich et al, 2006). The latter study has also demonstrated that impaired interactions between leukcocytes and vascular endothelium in this tumour coincided with elevated expression of immune-suppressive cytokine IL-10 by endothelial cells.…”
Section: Discussionmentioning
confidence: 96%